Confirmation of no impact from different anticoagulant counter ions on bioanalytical method. (April 2012) - Bergeron, Annik; Bergeron, Mélanie; Garofolo, Fabio
Background: In the past several years, the impact of changing counter ions while keeping the same anticoagulant in bioanalytical LC–MS/MS methods has become a highly discussed topic. In order to confirm that there is no impact from counter ions, matrix effect and stability evaluations were performed on bicalutamide LC–MS/MS bioanalytical methods.Results: Independently from the anticoagulant counter ion used, the matrix effect evaluation met acceptance criteria, even when using conditions expected to increase matrix effect, such as protein precipitation with an analog internal standard. Freeze–thaw along with storage stabilities, namely short- and long-term, demonstrated less than 8% deviation regardless of the counter ion used.Conclusion: Differences in the anticoagulant counter ion used has no impact on the bicalutamide bioanalytical LC–MS/MS method.